(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2023)
In a previous article in this journal, December issue, we discuss among other things Potential use of water as fuel for cars etc, as per inventions by Puharich, Stan Meyer etc. Meanwhile, we acknowledged that such ideas are met with skepticism by many physicists, partly because experimenting with molecule resonance is not quite accepted yet. Therefore in this short review, we discuss a number of scientific reasoning to support experiments and patents such as by Dr Andrija Puharich and Stan Meyer et al. We argue for tetrahedral structure of water molecule, and then how certain frequency pulse input can trigger molecular resonance effect as per required for efficient electrolysis, and then we discuss possible interaction between low level laser pen and water molecule.